Democratic Republic of Sao Tome and Principe : Request for a 40-month Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Democratic Republic of Sao Tome and Principe. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Democratic Republic of Sao Tome and Principe's Request for a 40-Month Arrangement Under the Extended Credit Facility (ECF). The ECF aims to support Sao Tome and Principe's economic and structural reforms. The program aims to reduce debt vulnerability, alleviate balance of payment pressures, restore fiscal and external sustainability over the medium term, promote sustainable and inclusive growth, and provide positive signals to stakeholders. Structural reforms should help mobilize revenue, enhance control over public spending, reduce contingent liabilities from state owned enterprises, improve financial stability, and promote sustainable and inclusive growth to reduce poverty, including through empowering women economically. The government plans to undertake sustained fiscal consolidation and reforms to reduce debt vulnerability. A floor on pro-poor spending, along with a World Bank social protection program, will protect the most vulnerable. The Fund-supported program will also play a catalytic role and provide positive signals to stakeholders.